Performance Audit Effectiveness Indicators: Evidence from Poland - Bednarek, Piotr; Ciak, Jolanta (Journal of Public Governance, 2022)
Objective: Performance audits, conducted by both internal and external auditors in public administration, play a crucial role in assessing effectiveness. This research focuses on the experiences of the Supreme Audit Institution (SAI) in Poland, delving into the effects of performance audits. Previous studies from selected developed countries shed light on performance audit impact, categorised as instrumental, conceptual, interactive, and political-legitimating. However, the generalisability of these findings is constrained by limited research, varying institutional and social contexts, and country-specific factors. To address these gaps, the authors of his study aim to expand knowledge on performance audit effectiveness indicators. Research Design & Methods: The research combines a literature review, analytical induction through interviews with SAI executives, and analysis of SAI activity reports from 2019–2021. Findings: The study reveals diverse interpretations of performance audit effectiveness among SAI delegation directors, encompassing process, results, and effects. Additionally, the research identifies indicators relevant to assessing performance auditing effectiveness in the Polish context. It emphasises the need for context-specific evaluations due to differing institutional and social conditions across countries. Implications/Recommendations: While acknowledging limitations, including the small sample size, this pilot study paves the way for future research to validate its hypotheses, explore factors influencing performance audit effectiveness, and compare practices across countries. Ultimately, it aims to enhance the effectiveness of performance audits in public administration. Contribution / Value Added: This research contributes to academia and practice by offering comprehensive performance audit effectiveness indicators. It introduces a novel indicator related to reporting infringements in public finance law and discipline.